The impact of coal mining on community health disorders around PT. Pacific Coal Mining - Asri, Haqan Hari; Yuniarti, Elsa; Razak, Abdul; Handayuni, Linda (Institute of Computer Science (IOCS), 2023)
Coal is a sedimentary rock whose main ingredient consists of carbon resulting from the formation of plant remains that have experienced heat and geological pressure for millions of years. Coal mining activities cause air pollution and are a negative externality that has an impact on health problems in the community. This research was conducted at PT. Pacific Coal Mining uses a qualitative descriptive method, data collection is carried out by direct observation of the impacts arising from coal mining activities. The results of this research arebased on people's habits in terms of washing, bathing and drinking, the majority use river water. Nutritional adequacy and food adequacy are considered sufficient. Furthermore, regarding the type of disease, the majority of respondents (83.33%) admitted that their family members had suffered from illness. The illnesses suffered include 40.00% upper respiratory tract infections/ARI (flu, coughs and colds), 26.67% suffering from malaria/chilling fever, 3.33% suffering from digestive tract diseases (diarrhea, dysentery and vomiting), and 13.33% suffered from other diseases, such as rheumatism, swollen legs and high blood pressure. As for health services, the health service facilities available at the study object are still very limited.